Electrical Properties Enhancement of Carbon Nanotube Yarns by Cyclic Loading - Weizman, Orli (Molecules, 2020)
Carbon nanotube yarns (CNTYs) possess low density, high conductivity, high strength, and moderate flexibility. These intrinsic properties allow them to be a preferred choice for use as conductive elements in high-performance composites. To fully exploit their potential as conductive reinforcing elements, further improvement in their electrical conductivity is needed. This study demonstrates that tensile cyclic loading under ambient conditions improves the electrical conductivity of two types of CNTYs. The results showed that the electrical resistance of untreated CNTYs was reduced by 80% using cyclic loading, reaching the resistance value of the drawn acid-treated CNTYs. Scanning electron microscopy showed that cyclic loading caused orientation and compaction of the CNT bundles that make up the CNTYs, resulting in significantly improved electrical conductivity of the CNTYs. Furthermore, the elastic modulus was increased by 20% while preserving the tensile strength. This approach has the potential to replace the environmentally unfriendly acid treatment currently used to enhance the conductivity of CNTYs.